National Geographic book of mammals (Washington, D.C. : The Society, 1981)
A picture encyclopedia presenting a general introduction to the world's mammals and the vital statistics and behavior for each of the entries from aardvark to zorilla.
Includes index.
Keywords: Mammals -- Encyclopedias, Juvenile; Mammals -- Encyclopedias